Pendampingan Ibu Rumah Tangga Dalam Meningkatkan Kedisiplinan Shalat Fardhu Anak - Makniyah, Jauharaotul; Choiriyah, Siti (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Children are a gift from Allah SWT, which we must be grateful for and take care of. Therefore, this period must be maximized to instill all kinds of virtues and disciplinary values ​​that can cleanse the soul to educate children so that they grow up to be human beings who have a strong personality, are not easily swayed by circumstances, believe sincerely in Allah SWT. and His apostles, and firm and strong in facing all kinds of life's problems. To improve child discipline, especially in worship, it is necessary to have a mother as the main support, because the closeness between mother and child is the main basis in guiding children to become better individuals, especially in improving the discipline of children's fardhu prayers. Therefore, a mother's assistance plays an important role in guiding children to be more disciplined in carrying out the five daily prayers because basically parents, both mothers and fathers, are madrasah or the first teacher for a child who fills in learning at home (informal)